The Characteristics of Patients at the Pulmonology Clinic of Dr. RM Djoelham Regional Hospital Binjai for the Period of January 2023 - June 2024 - Arsyad, M. Hatadi; Tabrani, Irma; Efriyandi, Efriyandi; Hervina, Hervina (International Journal of Public Health Excellence (IJPHE), 2024)
Healthy lungs are vital in sustaining respiratory function and oxygen balance in the human body. Diseases in the lungs can cause decreased function in the lungs and result in various health problems and disruption of a person's quality of life therefore we also require certain lung diseases that often occur in the community. Diseases of the lungs have diverse causes, treatments, and measures of prevention depending on the diagnosis. In this study, various lung disorders that are regularly experienced in the community are discussed, which we need to know Method: retrospective descriptive research with a cross-sectional design with the means of data collection, namely secondary data from new patient visits for treatment and have been diagnosed with lung disease and recorded in the Medical Record of the Pulmonology Polyclinic of Dr. RM Djoelham General Hospital from January 2023 to June 2024. Results: the number of research samples was 446 patients where the prevalence of patients with the most diagnoses was pulmonary tuberculosis (TB) as many as 237 patients (53.1%), with the most age group of 51-60 years as many as 93 patients (20.9%), the most male sex as many as 266 patients (59.6%) and the most are jobs as non-ASN/private as many as 193 patients (43.3%) and the most education is high school graduates / equivalent as many as 237 patients (53.1%). Conclusion: If there is a disturbance in the respiratory system, immediately examine yourself as early as possible to get best treatment and avoid complications that might cause death.